GAYA KEPEMIMPINAN, DESENTRALISASI SEBAGAI VARIABEL MODERATING DALAM HUBUNGAN ANTARA PARTISIPASI PENYUSUNAN ANGGARAN DENGAN KINERJA MANAJERIAL - Rosyati, Rosyati; Fajriyah, Anni Fajriyah (Jurnal Analisis Bisnis Ekonomi, 2005)
Planning in a company, budget is top-drawer component. Budget is containing planning concerning monetary plans summary of organization in the future. Budget personate performance criterion weared as operation system to measure performance of manajerial. Effective performance is if intention of tired budget and participation of subordinate hold important role in attainment of target. This research will test factors influencing relation between participation compilation of performance and budget of manajerial by using approach of contingency. Factor the used is leadership style relate to factor of situasional decentralization and as factor of kontekstual organisasional. Leadership style and decentralization used as by approach of coningency in this research because both the factor can influence environment palnning of organization. Target to reach in this research is to test imperically how far leadership style and decentralized authority what overflows degree the functioningness as variable of moderating influence relation between budget participation with performance of manajerial. To support and reach target and also intend this research is used by method analyze simple linear regression and interaction test for the model research. The quality of data use validity test and test of reabilitas. Level of independent variable contribution to variable of dependen shown with coefficient test of determinasi (test R). Text Hypothesis use test of F and test t. Research result obtained by evidence that there is relation which isn't it between budget participation with performance of manajerial, existence of positive relation between budget participation with decentralization to performnace manajerial, and there no relaion between budget participation with style leadership of performance between manajerial. persuant to research result, suggested that by manufacturing business in Magelang, Temanggung, and Purworejo in compilation of budget entangle middle manager so to be can participate and apply system secentralize so that will improve performance on manajerial.